Determination of Flavonoid Levels and Anti-Inflammatory Activity of Lime Root Extract (Citrus aurantifolia) by Granuloma Pouch Method - Yusuf Anggoro Mukti; Rohama Rohama; Ghina Raudhatul Jannah; M. Iqbal Rizantha; Muhammad Alfian Daud (Berkala Kedokteran, 2025)
Non-communicable diseases (NCDs) are still the leading cause of death at the global level. In Indonesia, NCDs contribute 71% of the total mortality rate. One of the causes of non-communicable diseases is the occurrence of oxidative stress in the body which is a condition of imbalance between free radical compounds and antioxidants. One of the sources of free radical formation in the body is when the inflammatory process occurs. Lime is used by the Indonesian people as a seasoning for cooking or empirically as an appetite enhancer, antipyretic and antibacterial. Research states that  lime root extract has very strong antioxidant activity with an IC50 value of 24.81 ppm and positively contains alkaloids, flavonoids, saponins and tannins. Flavonoids are thought to act as antioxidants and anti-inflammatory through their ability to donate hydrogen atoms and the ability to bind prostaglandins, COX-1 and COX-2 and lipooxygenase enzymes. The very strong antioxidant activity and the presence of flavonoids contained make lime root have the potential as an anti-inflammatory. Determination of flavonoid levels of lime root extract using UV-Vis spectrophotometry method with quercetin as a comparison and testing of anti-inflammatory activity of lime root extract using the Granuloma Pouch  method using mouse test animals. The results showed that the total flavonoid level was 36.8 mg QE (Quersetin Equialen)/g or 3.68%. And itexerts an anti-inflammatory effect through its ability to reduce the volume of exudate, lower the total exudate leukocytes, and lower the number of neutrophils in the exudate, most notably at a concentration of lime root extract of 20%.